Chronotype predicts positive affect rhythms measured by ecological momentary assessment. (April 2015) - Miller, Megan A.; Rothenberger, Scott D.; Hasler, Brant P.; Donofry, Shannon D.; Wong, Patricia M.; Manuck, Stephen B.; Kamarck, Thomas W.; Roecklein, Kathryn A.
<x xml:space="preserve">Abstract</x> Evening chronotype, a correlate of delayed circadian rhythms, is associated with depression. Altered positive affect (PA) rhythms may mediate the association between evening chronotype and depression severity. Consequently, a better understanding of the relationship between chronotype and PA may aid in understanding the etiology of depression. Recent studies have found that individuals with evening chronotype show delayed and blunted PA rhythms, although these studies are relatively limited in sample size, representativeness and number of daily affect measures. Further, published studies have not included how sleep timing changes on workday and non-workdays, or social jet lag (SJL) may contribute to the chronotype-PA rhythm link. Healthy non-depressed adults (n = 408) completed self-report affect and chronotype questionnaires. Subsequently, positive and negative affects were measured hourly while awake for at least two workdays and one non-workday by ecological momentary assessment (EMA). Sleep variables were collected via actigraphy and compared across chronotype groups. A cosinor variant of multilevel modeling was used to model individual and chronotype group rhythms and to calculate two variables: (1) amplitude of PA, or the absolute amount of daily variation from peak to trough during one period of the rhythm and (2) acrophase, or the time at which the peak amplitude of affect rhythms occurred. On workdays, individuals with evening chronotype had significantly lower PA amplitudes and later workday acrophase times than their morning type counterparts. In contrast to predictions, SJL was not found to be a mediator in the relationship between chronotype and PA rhythms. The association of chronotype and PA rhythms in healthy adults may suggest the importance of daily measurement of PA in depressed individuals and would be consistent with the hypothesis that evening chronotype may create vulnerability to depression via delayed and blunted PA rhythms.